Penegakan Hukum Terhadap Anak Pelaku Tindak Pembunuhan - Ni Nyoman Dara R.D; Tofik Yanuar Chandra; Mohamad Ismed (Jurnal Penelitian Hukum Legalitas, 2023)
Children are in an environment that increasingly leads to criminal acts, one of which is murder. In law enforcement, problems arise because the perpetrators of these crimes are children who do not yet have legal capacity. In Indonesia, law enforcement against children who commit murder has been regulated in Law Number 11 of 2012 concerning the Child Criminal Justice System with the aim that the legal process is different from adults. The method in this research is normative juridical. The result of this research is law enforcement against children who commit murder in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, can be sentenced to the main criminal sanction, namely imprisonment formulated in Article 81 paragraph (2), "The imprisonment that can be imposed on children is at most 1/2 (one half) of the maximum imprisonment for adults